2019
DOI: 10.1186/s13104-019-4794-y
|View full text |Cite
|
Sign up to set email alerts
|

Body composition indices in a sample of female adolescents with postural deformity: a case control study

Abstract: ObjectivesNormal posture is considered to be an indicative of good musculoskeletal health in school aged adolescents. Little is known about the body composition indices in relation with postural deformities in adolescents. The aim of this study was to assess relation of body composition analysis indices with postural deformities in a sample of female high school adolescents.ResultsIn this case–control study, 37 eligible female adolescents with any postural deformities and 33 normal posture subjects enrolled in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Additionally, variable lordosis is more common among female participants ( 14) compared to male participants (5). The variable flatback outlier deformity of the lumbar spine, representing a sagittal imbalance, is also more prevalent among male participants (27) compared to female participants (11). Furthermore, the variable kypholordosis is more prevalent among female participants (66) compared to male participants (18).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, variable lordosis is more common among female participants ( 14) compared to male participants (5). The variable flatback outlier deformity of the lumbar spine, representing a sagittal imbalance, is also more prevalent among male participants (27) compared to female participants (11). Furthermore, the variable kypholordosis is more prevalent among female participants (66) compared to male participants (18).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, recent studies show a continuous rise in the prevalence of postural outliers, reported as a percentage [8]. The trend of an increased occurrence of poor posture among adolescents in the Republic of Serbia is also evident in neighboring countries within the Western Balkans region [9,10], as well as globally [6,11].…”
Section: Introductionmentioning
confidence: 99%
“…The same positive influence on reducing the deviation from the typical bodily alignment in the anteroposterior orientation was observed for PFFM (−0.531). Golalizadeh et al [41], in a study with somewhat older girls (14-18 years of age), found that fat-free mass had a protective effect against postural disorders. When analyzing the influence of body composition relative to gender, it is evident that, in both boys and girls, PSMM and PFFM exert a beneficial impact on reducing the likelihood of deviating from normal body posture in the sagittal plane.…”
Section: Discussionmentioning
confidence: 97%